Direct measurement of thermophoretic and photophoretic force acting on hot micromotors with optical tweezers; Applied Surface Science; Vol. 549 - Frueh J. С. Johannes Christoph; Rutkowski S. Sven; Si T. Tieyan; Ren Yu. Yuxuan; Gay M. Meyu; Tverdokhlebov S. I. Sergei Ivanovich; Qiu G. Guangyu; Schmitt J. Jean; He Q. Qiang; Wang J. Jing (2021, 2021)
Title screen